2005
DOI: 10.2320/matertrans.46.2190
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Potential and pH on Initiation of Environment-Assisted Cracking of Ti–6Al–4V

Abstract: We have investigated the influences of potential and pH on environment-assisted cracking (EAC) of Ti-6Al-4V in aqueous solutions. The EAC test was conducted by slow strain rate technique. Solution pH was controlled from 1 to 7, and applied potential was fixed between À1:8 and þ0:2 V SHE . In the solutions of pHs 3 and 7, mechanical properties of the material was almost independent of applied potential. This means that the material shows almost no EAC susceptibility in the potential-pH region for the EAC test p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…These ndings suggested that the surface property relating to the process of hydrogen absorption was not affected by Al, but was affected by Ti. Our research group also previously produced an EAC map of Ti-6Al-4V alloy 13) and a hydrogen absorption map of Ti 14) ; and revealed that these Ti-Al alloys, including Ti, absorbed hydrogen most severely in the Ti ion stable region. Conversely, no stable regions for chemical species except for hydrogen could be identi ed on the potential-pH diagrams of the Ni/H 2 O and Ti/H 2 O systems that corresponded to the region of severe EAC susceptibility.…”
Section: Surface Conditions Of Tini Alloy For Absorption Of Hydrogenmentioning
confidence: 99%
“…These ndings suggested that the surface property relating to the process of hydrogen absorption was not affected by Al, but was affected by Ti. Our research group also previously produced an EAC map of Ti-6Al-4V alloy 13) and a hydrogen absorption map of Ti 14) ; and revealed that these Ti-Al alloys, including Ti, absorbed hydrogen most severely in the Ti ion stable region. Conversely, no stable regions for chemical species except for hydrogen could be identi ed on the potential-pH diagrams of the Ni/H 2 O and Ti/H 2 O systems that corresponded to the region of severe EAC susceptibility.…”
Section: Surface Conditions Of Tini Alloy For Absorption Of Hydrogenmentioning
confidence: 99%
“…For titanium alloys, such as Ti6Al-4V alloy, however, the hydrogen absorption behavior is not necessarily consistent with the electrochemical behavior. 21,22) In addition, the hydrogen absorption behavior of Ti-6Al-4V alloy strongly depends on the type of solution. In this case, the hydrogen absorption behavior appears to depend on the surface conditions, including the nature of surface oxide films on titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that for Ti-6Al-4V alloy, corrosion does not necessarily lead to hydrogen absorption in fluoride solution, although for commercial pure titanium, corrosion leads to hydrogen absorption. 17) In aqueous Na 2 SO 4 solutions with pH ranging from 3.0 to 7.0, as reported by Haruna et al, 18) hydrogen-induced environment-assisted cracking of Ti-6Al-4V alloy does not occur even under a cathodic potential of À2:0 V. In addition, we have recently demonstrated that the hydrogen absorption of Ti-6Al-4V alloy occurs below the cathodic potential of À1:9 V in neutral 2.0% NaF solution. 16) In the present study, however, Ti-6Al-4V alloy absorbed substantial amounts of hydrogen in APF solutions with concentration of 0.4% and higher under a corrosion potential of À1:0 V. Furthermore, although electrochemical behavior was not significantly different between 1.5% and 2.0% APF solutions, the amount of absorbed hydrogen depended on the concentration of APF solution.…”
Section: Discussionmentioning
confidence: 96%